Studi Pemahaman ECO Riding Mahasiswa Program Studi Pendidikan Teknik Otomotif - Widiyatmoko Widiyatmoko; Mike Elly Anitasari; Aci Primartadi; Muhammad Abdul Wahid (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Eco riding/driving is an approach to driving that aims to optimize fuel efficiency and reduce environmental impact. This technique guides drivers to avoid sudden acceleration and braking in order to maintain a stable speed, maintain optimal tire pressure and carry out regular vehicle maintenance. This technique helps save fuel, reduces greenhouse gas emissions, and extends vehicle life. The aim of this research is to determine the level of understanding of students in the automotive engineering education study program regarding Eco Riding. This research is a survey research carried out from July - December 2024 to 56 students in the automotive engineering education study program at Muhammdiyah University, Purworejo. The research data were analyzed using quantitative descriptive analysis. The research results showed that the level of students' understanding of Eco Riding was in the high category at 50%, followed by the medium category (32.1%), rendang category (14.3%) and very high category at 3.6%.